Peningkatan Hasil Belajar Matematika Materi Bangun Ruang Melalui Penggunaan Media Tiga Dimensi pada Siswa.pdf (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to improve mathematics learning outcomes through three-dimensional media in fifth grade students at SDN 24 Toboali. This research is a type of classroom action research. The research subjects were fifth grade students at SD Negeri 24 Toboali. The object of research is the results of learning mathematics in class V students. Data collection techniques use observation, written tests, and documentation. This research was said to be successful if 80% of students achieved KKM, namely 68. The results showed that the completeness of student learning outcomes in cycle I and cycle II experienced a significant increase. The average score of students who completed the first cycle was 62.35 and in the second cycle it increased to 79.41. In cycle I, the percentage of students who passed was 47.05% and in cycle II it rose to 82.35%. Then the assessment of students' attitude of responsibility in cycle I was 72%, it increased in cycle II to 83.75%, the assessment of student discipline in cycle I was 66%, it increased in cycle II to 89.5%, and the assessment of students' self-confidence in the first cycle of 58.75% increased in the second cycle to 82.25%. Based on the data above, it can be concluded that classroom action research has met the success criteria and is proven to be able to improve the learning outcomes of fifth grade students at SDN 24 Toboali.